VOKS, Cultural Diplomacy and the Shadow of the Lubianka: Olavi Paavolainen’s 1939 Visit to the Soviet Union - Ville Laamanen (Sage Publications Ltd., 2022)
Existing scholarship suggests that Stalin’s Great Terror of 1936–8 seriously undermined Soviet cultural diplomacy and forced its main promoter, the All-Union Society for Cultural Relations with Foreign Countries (VOKS), to succumb to the strict control of the party and secret police. By contrast, this article argues that by the spring and summer of 1939 VOKS was recovering from stagnation and reintroducing customs from before the Great Terror. Through a micro-historical analysis of Finnish writer Olavi Paavolainen’s exceptionally long visit to the Soviet Union between May and August 1939, the article demonstrates how case studies of select VOKS operations can explain many of the dilemmas and peculiarities of Soviet cultural diplomacy during the thus far scantily researched 1939–41 period. By focusing on the interactions between Paavolainen, the VOKS vice-chairman Grigori Kheifets and Soviet writers, the article illustrates that after the purges, VOKS continued its efforts to disseminate a positive and controlled image of Soviet life by complex means that linked propaganda with network-building. Finally, the article highlights the role of individuals in cultural diplomacy and explores how an outsider perceived the Great Terror’s effects on Soviet cultural intelligentsia.